Accident Analysis Using Case Studies of Finger Injuries at PT X Mining Company in 2020-2022 - Prihatsono, Nurcahyo Kurniawan; Erwandi, Dadan (Riwayat: Educational Journal of History and Humanities, 2024)
Mining activities are known as high-risk working environments and operational activities, they are categorized as one of the most dangerous activities in modern industry today. The mining industry ranks among the highest producers of injuries and lost working days. There are many types of injuries that contribute to this lost working days, finger injury is one of them. Fingers are reported to be one of the most injured body parts. This research carried out on a mining company in Indonesia, PT X, within a period of three years (2020-2022). Statistical analysis was performed to look for patterns of finger injury based on year of occurrence, classification, type, and source of injury, number of lost working days, type of employee, and business unit involved. There is an alarming upward trend in the number of finger injuries and lost working days resulting from them, although overall the number of injuries has decreased. This calls for immediate preventive measures to focus on finger injuries and focuses on changing worker behavior towards safe work behavior, applied to both permanent employees and contractor employees.